Pyrrolо[1,2-a]azolo-(azino-)[c]quinazolines and their derivatives as 15-LOX inhibitors: Design, in vitro studies and QSAR-analysis - Krasovska, N.; Stavytskyi, V.; Nosulenko, I.; Kholodniak, S.; Antypenko, O.; Voskoboinik, O.; Kovalenko, S.; Ставицький, Віктор Валерійович; Носуленко, Інна Степанівна; Холодняк, Сергій Валерійович; Антипенко, Олексій Миколайович; Воскобойнік, Олексій Юрійович; et al. (My University, 2021)
Present manuscript is devoted to the search of 15-LOX inhibiting agents among pyrrolo[1,2-a]azolo-(azino- )[c]quinazolines using in silico and in vitro methods. Molecular docking method was used for calculation of affinity and evaluation of protein ligand interactions features. Colorimetric in vitro assay was used for estimation of LOX-15- inhibiting activity of synthesized compounds. QSAR-analysis was used for formation of the models applicable for prediction of properties of not yet synthesized inhibitors of 15-LOX. It was shown that some of the studied compounds reveal LOX-inhibiting activity that was comparable or higher than activity of the reference compound – Nordihydroguaiaretic acid. The conducted molecular docking study allowed to elucidate the affinity towards the enzyme. The visualization of docking study results allowed to establish and to discuss the features of ligand – 15-LOX interactions. The correlations between structure, LOX-inhibiting activity, calculated affinity and lipophilicity were considered as well. The performed QSAR-analysis resulted the five parametric linear model that like docking study results are valuable for further search of promising 15-LOX-inhibitors. Pyrrolo[1,2-a]azolo-(azino-)[c]quinazolines were identified as 15-LOX inhibitors. The reliable correlation between 15-LOX inhibiting activity of the synthesized compounds, their lipophilicity and calculated affinity was not observed. Visualization of molecular docking results and formed QSAR-models may be used as theoretical basis for novel LOX-inhibitors design.
Keywords: Pyrrolo[1,2-a]azolo-(azino-)[c]quinazolines; 15-lipoxygenase; molecular docking; inhibitors; SAR; QSAR-analysis